Smartphone and Self-Harm: A study of TikTok Use as a Risk Factor - Udam, Mikhael; Oktara, Tri Windi; Justitia, Dewi; Putri, Utami Nurhafsari; Karisma, Sally Putri; Fajri, Nurul; Muhazir, Muhazir; Erwinda, Lira (Kuras Institute, 2024)
In recent years, the use of social media and the internet has become an inseparable part of everyday life, especially among adolescents. Social media offers a variety of benefits, including ease of communication, access to information, and entertainment. However, concerns have emerged about its negative impact on mental health, especially in relation to self-harm behavior. Adolescents often imitate the trend of self-harm and join in posting the results of scratches on social media. The aim of this study was to determine variations in self-harm in adolescents which are related to the duration of internet use in one day and the use of social media. The research method uses a comparative descriptive approach and Two-Way ANOVA analysis to explore interactions between these variables. Data was collected through an online survey with a self-harm instrument consisting of 18 statements, with respondents choosing from 4 alternative answers available. The results of the analysis show that there are significant differences in self-harm behavior based on the duration of internet use per day and the type of social media used. Adolescents who use the TikTok platform show a higher self-harm score compared to other platforms, especially with longer duration of internet use. These findings indicate that the type and way of using social media has a significant influence on self-harm behavior.